Основы рационального освоения недр КМА - Щеголев И. Н. Игорь Николаевич; Селезнев В. Н. Виктор Николаевич; Кирьянчук В. Е. Виктор Евгеньевич; Щербаков А. П. (Воронеж, Изд-во Воронеж. ун-та, 1991)
Авт. указаны на обороте тит. л.